Prevalence of Access to Prenatal Care in the First Trimester of Pregnancy Among Black Women Compared to Other Races/Ethnicities: A Systematic Review and Meta-Analysis - Pedro Henrique Alcântara da Silva; Kezauyn Miranda Aiquoc; Aryelly Dayane da Silva Nunes; Wilton Rodrigues Medeiros; Talita Araujo de Souza; Javier Jerez-Roig; Isabelle Ribeiro Barbosa (Public Health Reviews, 2022)
Objective: To analyze the prevalence of access to prenatal care in the first trimester of pregnancy among black women compared to other races/ethnicities through a systematic review and meta-analysis.Methods: Searches were carried out at PUBMED, LILACS, Web of Science, Scopus, CINAHL, and in the grey literature. The quality of the studies and the risk of bias were analyzed using the Joanna Briggs Critical Appraisal Checklist for Analytical Cross-Sectional Studies instrument. The extracted data were tabulatesd and analyzed qualitatively and quantitatively through meta-analysis.Results: Black women had the lowest prevalence of access to prenatal services in the first trimester, with prevalence ranging from 8.1% to 74.81%, while among white women it varied from 44.9 to 94.0%; 60.7% of black women started prenatal care in the first trimester, while 72.9% of white women did so.Conclusion: Black women compared to other racial groups had lower prevalence of access to prenatal care, with less chance of access in the first trimester, and it can be inferred that the issue of race/skin color is an important determinant in obtaining obstetric care.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020159968_, PROSPERO CRD42020159968.